Mapping the Resources of First High School Educators in East Jakarta - Hamid Al Jufri (Institute of Computer Science (IOCS), 2022)
The problem of this research is that there are still many unprofessional teachers because teachers are the spearhead of the advancement of a nation. The purpose of this study was to determine the education level, status, certification, and age of junior high school teachers in East Jakarta. The population in this study were all teachers in East Jakarta. Data collection techniques were carried out by means of documentation and questionnaires. To get an accurate assessment, the assessment of the results of the questionnaire is carried out with a descriptive quantitative assessment. The results of the study show that there are still 491 high school teachers, 2416 auxiliary and honorary teachers, and 2391 who have not been certified, and there is still a lack of young teachers. Based on the results of this study, it is suggested that public schools in East Jakarta need to increase the level, status, and certification of teachers, and consider age in accepting teachers.